Water charging and water saving in agriculture. Insights from a Revealed Preference Model in a Mediterranean basin. (July 2015) - Pérez-Blanco, C. Dionisio; Delacámara, Gonzalo; Gómez, Carlos M.
Abstract: The large irrigation expansion of the last 50 years has increased pressure on water resources in EU Mediterranean basins. Water charging has been encouraged, since within the EU policy context it is believed that higher charges reduce water use. This paper presents a Revealed Preference Model that provides a clear intuition of the logic behind farmers' choices using standard economic analysis and implementing a multi-attribute utility function. The model is calibrated for the profitable Agricultural Districts (ADs) in the overexploited Segura River Basin (SRB) in southeastern Spain. Results show that water use is highly inelastic for charge increases below 0.5 €/m 3 (i.e. a water charge increase of 600%), and only starts showing a significant reduction for water charges above this threshold. However, water charging can still be used to promote the swap of overused and inexpensive conventional resources by underused and more expensive desalinated water. Highlights: It is widely accepted that higher water prices reduce water demand. We develop a Revealed Preferences Model to assess farmers' response to higher prices. The model is calibrated for the highly productive and overexploited Segura RB, Spain. Higher prices reduce the gross margin, but water demand is found highly inelastic. Water prices per se may be ineffective to reduce water use.